PERANAN TULANGAN TEKAN PADA BALOK TERLENTUR TULANGAN RANGKAPUNTUK MEMBANGKITKAN MOMEN NOMINAL - Puryanto Puryanto (PILAR, 2013)
Installation  of  compression  reinforcement  in  the flexural beam  can  not  be  avoided  .  Two  things which are coercive ,ie tying  stirrup  and high of  beam restricted by the architect . Flexural beam  is calculated  based  on  the  design  moment  .  Design  moment    is  the  nominal  moment  multiplied  by reduction factor Φ . Nominal moment is the sum of the two parts of the nominal moment . The first nominalmoment call Mn1  , ie couple between tensile force of the first tensile reinforcement  NT1 = As1.fy with concrete compressive force ND = 0.85 fc '.a.b . Second nominal moment Mn2 , which is couple between the second tensile reinforcement force NT2 = As2.fy with the force of compression reinforcement    ND  '  =  As’.  Fs'  .  By  adding  compression  reinforcement    is  expected  to  rise  as  well nominal moment . After analyzed here are four conclusions can be drawn .First , the beam does not always require  compression  reinforcement  .  Second  ,  if  the  compression  reinforcement  is  installed too   deep   will   cause its stress   decreases   ,   it   can   even   be   ignored.   Third   ,   the   compression  reinforcement  additional  is  not  comparable  with  the    nominal  moment  increament.  The  more aditonal of the compression reiforcement  , the smaller the ratio of nominal moment we get. Fourth , the  increase in the  second nominal moment Mn 2 can continue to be done by the limit only by the availability of the place of installation.